The possible anti-inflammatory effect of extra virgin olive oil with colchicine in treatment of resistant cases of familial Mediterranean fever in a cohort of pediatric Egyptian patients - Walla’a A. Osman; Heba Taher; Hanan Darweesh; Mai Abdel Samie; Olfat G. Shaker; Dina A. Labib; Hayam Ateyya (Future Journal of Pharmaceutical Sciences, 2024)
Abstract Background People of Mediterranean descent are primarily affected by the autoinflammatory genetic condition known as familial Mediterranean fever (FMF). The disease is resistant to colchicine therapy in 10–20% of patients. Numerous recent animal studies showed promising results of extra virgin olive oil (EVOO) to control inflammation. The objective of this study was to assess the effectiveness of combining EVOO with colchicine in the treatment of colchicine-resistant familial Mediterranean fever (CRFMF) patients. Results Both the frequency of episodes and inflammatory indicators significantly decreased after a three-month course of daily EVOO treatment with colchicine. The average erythrocyte sedimentation rate (ESR) of patients was 78.6 mm/h before the EVOO administration, and it dropped to 27.8 mm/h, after that. Additionally, after taking EVOO, the mean serum amyloid A (SAA) decreased from 123.82 mg/dl to 59.78 mg/L. Also, the average C-reactive protein (CRP) decreased from 34.22 to 7.84 mg/dl following its administration; the mean nucleotide-binding domain, leucine-rich-containing family, and pyrin domain-containing-3 (NLRP3) level decreased from 134.92 to 64.23 pg/ml. The mean caspase-1 level decreased from 7.8 to 4.98 ng/ml; and the mean levels of cytokines, interleukin 6 (IL-6), interleukin 1 beta (IL-1 β), and tumor necrosis factor-alpha (TNF-α) decreased from 9.8, 18.14, and 52.7 pg/ml, respectively, to 5.95, 12.51, and 29.39 pg/ml. Finally following the administration of EVOO, there was a notable overall improvement in the quality of life of (CRFMF) patients. Conclusion EVOO demonstrated a significant positive impact when paired with the tolerated dosage of colchicine in the management of CRFMF. Improvements were observed in both clinical and laboratory settings, including a reduction in the attack frequency and serum levels of inflammatory markers, such as NLRP3, caspase-1, ESR, CRP, IL-1β, IL-6, and TNF-α without any negative side effects.